1982
DOI: 10.1177/019262338201000208
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of altered hepatocytes induced by diethylnitrosamine (DENA)

Abstract: Administration of diethylnitrosamine I.P. at dose level of 2 mg/kg five days a week to young Sprague-Dawley rats induced foci of altered hepatocytes entirely devoid of glucose-6-phosphatase and adenosine triphosphatase activity. Several weeks later, these foci developed hepatocellular carcinoma mostly of the trabecular type. Although these "preneoplastic" altered cells appeared as normal hepatocytes when examined in HE-sections, they were found to exhibit sites of dedifferentiation with ultrastructural feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…DENA administration has been associated with morphological variation in hepatocytes, leading to their transformation into neoplastic cells. 27 Lesions in liver tissues have been reported earlier to be due to elevated levels of liver enzymes causing damage to the tissue. 28,29 The histopathological studies showed that DENA treatment caused complete distortion of liver histology and led to proliferation of bile ducts, anisocytosis, anisokaryosis and karyomegaly.…”
Section: Discussionmentioning
confidence: 98%
“…DENA administration has been associated with morphological variation in hepatocytes, leading to their transformation into neoplastic cells. 27 Lesions in liver tissues have been reported earlier to be due to elevated levels of liver enzymes causing damage to the tissue. 28,29 The histopathological studies showed that DENA treatment caused complete distortion of liver histology and led to proliferation of bile ducts, anisocytosis, anisokaryosis and karyomegaly.…”
Section: Discussionmentioning
confidence: 98%